Effect of resisted sled sprint with different loads on running velocity, step frequency, and step length - Takeru Hamamichi; Kiyotaka Naoi; Susumu Shigeta; Jorge Morais; Daniel Almeida Marinho; Shin-Ichiro Moriyama (Motricidade, 2024)
It has been shown that training with resistance sled sprints (RSS) can improve running performance, but the effect of different RSS loads on sprint performance is unclear. This study aimed to examine this effect on running velocity, step frequency, and step length. Twenty-one collegiate track and field male athletes (20.6 ± 1.3 years) performed eight 60-m sprints with and without a resisted sled. The sled loads were individually set based on the participant's body mass (BM) and were applied in 10% increments from 20%–80% of BM. A 20-minute rest was allowed between trials. The running distance was divided into six 10-m phases. We analyzed the mean running velocity, step frequency, and step length at each phase, observing significant interactions in each. All indices decreased with increasing loads. Significant differences were observed in running speed and step frequency between all loads, except between 70%–80% of BM, and in the step length between all loads. Additionally, the maximum values for running velocity, step frequency, and length appeared in different phases according to the load. In addition to kinematics, coaches and athletes should focus on setting running distances and loads in RSS training.